PERILAKU BERJUDI PADA REMAJA (STUDY TENTANG JUDI BILLIARD DI DESA PETAPAHAN JAYA KABUPATEN KAMPAR) - Yolanda Stepy; Hesti Asriwandari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This study is about “Gambling Behavior on Adolescent ( A Study About Billiard Gambling at Petapahan Jaya Village, Kampar District). Where the research intends to explain how the gambling activity among adolescent and the establishment of gambling behavior among adolescent at Petapahan Jaya village. In this research, the author used qualitative research, that is the research which are produced descriptive data in the form of written or spoken and explained data through reasoning based on logic to get the logical conclusion of the data in the analysis, so it can systematically describing the situation in accordance with the phenomenon that is being researched. The techniques of collecting data are used interview techniques, observation, and documentation. Based on the result of the research, the adolescent at Petapahan Jaya village used billiard as a gambling tools, which is the game or the gamble used playing cards and money, playing cards are used as the determinant ball number, what number will be included by the player according to the number on the card. While the money used as the bet, which are given to the winner, it means that the game is over, and this is the core of this game. This adolescent activity of gambling are often done, and almost everyday. While the establishment of the gambling behavior occurs because of environmental factors and playmates.Keywords: Adolescent, Behavior Gambling, Billiard Gambling